Fatty acyl desaturation in isolated hepatocytes from Atlantic salmon (Salmo salar): Stimulation by dietary borage oil containing gamma-linolenic acid - Tocher, Douglas R; Bell, J Gordon; Dick, James R; Sargent, John R (Lipids, 1997)
The effects of different dietary oils on the fatty acid compositions of liver phospholipids and the desaturation and elongation of [1-14C]18∶3n−3 and [1-14C]18∶2n−6 were investigated in isolated hepatocytes from Atlantic salmon. Atlantic salmon smolts were fed diets containing either a standard fish oil (FO) as a control diet, a 1∶1 blend of Southern Hemisphere marine oil and tuna orbital oil (MO/TO), sunflower oil (SO), borage oil (BO), or oliver oil (OO) for 12 wk. The SO and BO diets significantly increased the percentages of 18:2n−6, 18:3n−6, 20:2n−6, 20:3n−6, and total n-6 polyunsaturated fatty acids (PUFA) in salmon liver lipids in comparison with the FO diet. The BO diet also increased the percentage of 20:4n−6. Both the SO and BO diets significantly reduced the percentages of all n−3 PUFA in comparison with the FO diet. The OO diet significantly increased the percentages of 18:1n−9, 18:2n−6, total monoenes, and total n−6 PUFA in liver lipids compared to the FO diet, and the percentages of all n−3 PUFA were significantly reduced. With [1-14C]18:3n−3, the recovery of radioactivity in the products of Δ6 desaturation was significantly greater in the hepatocytes from salmon fed SO, BO, and OO in comparison with the FO diet. The BO diet also increased the recovery of radioactivity in the products of Δ5 desaturation. Only the BO diet significantly affected the desaturation of [1-14C]18:2n−6, increasing recovery of radioactivity in both Δ6- and Δ5-desaturation products. In conclusion, dietary BO, enriched in γ-linolenic acid (18:3n−6), significantly increased the proportions of both 20:3n−6 and 20:4n−6 in salmon liver phospholipids and also significantly increased the desaturation of both 18:2n−6 and 18:3n−3 in salmon hepatocytes. The possible relationships between dietary fatty acid composition, tissue phospholipid fatty acid composition, and desaturation/elongation activities are discussed.